Memorandum of understanding between Universiti Teknologi MARA and Geocon Engineering Sdn Bhd / Fakulti Kejuruteraan Awam - Universiti Teknologi MARA, Fakulti Kejuruteraan Awam (Universiti Teknologi MARA (UiTM), 2019)
UiTM and Geocon will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.